The technique of retrograde CBCT-sialography in obstructive parotid salivary gland syndrome - A. Ya. Razumova; A. A. Zubareva; A. I. Yaremenko; S. I. Kutukova; N. L. Petrov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Diagnosis of obstruction of the ductal system of the salivary glands is a difficult task. Standard research methods cannot detect such pathology. CBCT-sialography is a modern technique that will simplify and increase the informative value of diagnostics compared to an X-ray image.The objective was to study the possibility of visualizing the ductal system of the salivary glands by retrograde administration of a contrast agent using ultrasound navigation to perform cone beam tomography (CBCT-sialography).Methods and materials. On the basis of the oncological Department № 8 of the FSBEI HE I. P. Pavlov SPbSMU MOH, the patient underwent the installation of a subclavian catheter under ultrasound control into the duct expansion cavity through the skin. Next, a radiopaque preparation was introduced, and a cone-beam computed tomography of the maxillofacial region was performed.Results. Based on the results of the study, surgical intervention was performed. During control examinations, no pathological changes in the ductal system of the parotid salivary gland were detected.Conclusion. This article describes a clinical case of the successful use of CBCT-sialography. This technique with a low radiation load has shown high informativeness and can be performed on an outpatient basis. Therefore, it is necessary to accumulate clinical material to evaluate the effectiveness of the technique in various pathological changes in the salivary glands.